Effects of a School-Based Intervention Program to Promote Adolescents’ Active Commuting by Cycling - Rodrigo-Sanjoaquín, Javier; Abós, Ángel; García-González, Luis; Sevil-Serrano, Javier (MHSalud: Revista en Ciencias del Movimiento Humano y Salud, 2023)
Objective: This study aimed to evaluate the effects of a school-based intervention program on competence satisfaction, the predisposition to participate in a cycling Didactic Unit (DU) in Physical Education, and the behavior of commuting by bicycle.Method: The study had a quasi-experimental design without a control group, in which 98 Spanish students (M=13.95±0.67; 50% girls) from a high school participated. The intervention program based on supporting competence consisted of a cycling DU (12 sessions), a tutorial action plan (4 sessions), and an extracurricular activity.Results: An increase in competence satisfaction was found only in boys, and the predisposition towards cycling DU was found in both genders. Likewise, the states of "Action" and "Maintenance" in the behavior of commuting by bicycle increased by 39% in boys and 43% in girls.Conclusion: This multi-component program based on strategies to support competence effectively promotes active bicycle travel among adolescents.